Adaptation of relationship marketing as a response to changes in hospital management - Dobska, Monika (Луцьк: Вежа-Друк, 2023)
The specificity of medical services lies in the fact that it touches on the issues of health, i.e. the basic factor guaranteeing the demographic, social and economic development of the country. Therefore, not only health care, understood as activity for health, becomes important, but above all health care, which basically boils down to service activity, consisting in the provision of medical services that meet specific needs. The aim of the article is to define and indicate arguments as a possibility of implementing relational marketing as a management concept for hospitals.
Keywords: medical services; relational marketing; management concept for hospitals